Reliability of the Laboratory Risk Indicator for Necrotizing Fasciitis (Lrinec) Score for Early Diagnosis of Necrotizing Fasciitis - H. M, Martis Manohar; Shetty, Prathvi; B. R, Hegde (Journal of Diagnostics, 2015)
Objective: Necrotizing fasciitis is a surgical emergency often requiring prompt diagnosis and treatment. Delay in surgical intervention can have catastrophic results including death. The laboratory risk indicator for necrotizing fasciitis (LRINEC) score uses laboratory parameters to assess the severity of infection and helps in early recognition of necrotizing fasciitis. In this study, we collected the data of 40 patients diagnosed and treated as necrotizing fasciitis to validate the reliability of this score in early diagnosis of necrotizing fasciitis. Materials and methods: This is a retrospective study. Data of 40 patients admitted to Fr. Muller Medical College Hospital, Mangalore from August, 2012 to August, 2014 with a clinical diagnosis of Necrotizing fasciitis was analyzed and relevant statistical tests were applied to evaluate the reliability of the LRINEC score. Results: A total of 40 patients were included in the study. A LRINEC score of > 6 had a sensitivity of 93.10 %, specificity of 90.91%, positive predictive value of 96.43%, and negative predictive value of 83.33%. The most common organism isolated on culture was Staphylococcus aureus. Conclusion: The LRINEC score is an impressive diagnostic tool to differentiate between necrotizing fasciitis and other less severe soft tissue infections. It aids in early recognition of necrotizing fasciitis enabling prompt and appropriate treatment.